Kinetika reaksi alkyd resin termodifikasi minyak jagung dengan asam phtalat anhidrat - Heri Heriyanto; Rochmadi Rochmadi; Arief Budiman (Jurnal Rekayasa Proses, 2011)
Esterification of phthalic anhydrate with monoglyceride is a condensation reaction to form a linear chain polymer. The present work aimed at investigating reaction kinetics of alkyd resin modified with corn oil in the absence of catalyst. The work consisted of two steps i.e. alcoholysis and esterification. In the alcoholysis step, corn oil and glycerol were brought into reaction with a molar ratio of 1:2 at 250°C. Every 30 minutes during 3 hour reaction, reaction products were sampled to analyse the remaining free glycerol by iodometry method (FBI-AO2-03). In the esterification step, phthalic anhydrate was put in the batch reactor with a glycerol-phthalic anhydrate molar of 3:2. Samples were taken and the hydroxyl ions were analysed by acetate anhydrate method. The variables investigated in the present work were reaction temperatures varied from 230°C to 260°C and equivalent OH/COOH ratio from 1 to 1.25. Experimental results showed that alcoholysis of corn oil and glycerol could be carried out in a temperature range of 230°C to 260°C without the presence of catalyst. The effect of temperature on the reaction rate constant of monoglyceride and phthalic ester formation could be respectively written in the Arrhenius correlations as follows: k1 = 1.4647.104 exp (− 8237.7/???? ) g/mgeq.min k4 = 2.1398.109 exp (− 14142/???? ) g/mgeq.min